A morphological study of the genus Penthalodes (Acari, Prostigmata, Eupodoidea, Penthalodidae) with description of a new species - Jesionowska, Katarzyna (Zootaxa, 2010)
The morphology of representative species of the genus Penthalodes is reviewed. A new generic diagnosis and an identification key for adults of Penthalodes species is provided. Previous descriptions of Penthalodes ovalis from Alaska and Hawaii are considered as different species and named as P. alaskaensis (Strandtmann) sp. n. and P. hawaiiensis (Strandtman & Goff) sp. n., respectively. Penthalodes polonicus sp. n. is described and illustrated based on material collected in Poland.